Time-Dependent Distribution of Hydroxychloroquine in Cynomolgus Macaques Using Population Pharmacokinetic Modeling Method - Liu, Qi; Bi, Guofang; Chen, Guiying; Guo, Xuan; Tu, Siqi; Tong, Xiaolin; Xu, Man; Liu, Mengjie; Wang, Bei; Jiang, Hongliang; Wang, Jufeng; Li, Haiyan; et al. (Frontiers in Pharmacology, 2021)
To evaluate the biodistribution of hydroxychloroquine (HCQ) in cynomolgus macaques and receive dynamic quantitative relationship between plasma, blood, and lung tissue concentration using population pharmacokinetic modeling method, seventeen cynomolgus macaques were divided into six groups according to different HCQ dosing regimens over 5 days. The monkeys were euthanized and blood, plasma, urine, feces and ten tissues were collected. All the samples were prepared by protein precipitation and analyzed by HPLC-MS/MS detection. The population pharmacokinetics of HCQ in plasma, red blood cells and lung tissue was conducted and simulated via ADAPT program. Results demonstrated that the maximum concentration (Cmax) of HCQ was 292.33 ng/mL in blood and 36.90 ng/mL in plasma after single dose of 3 mg/kg. The value of area under curve (AUC0–∞) were determined as 5978.94 and 363.31 h∙ng/mL for blood and plasma, respectively. The descending order of the tissues to plasma concentration ratio was liver > spleen > kidney > lung > heart > subcutaneous fat > brain. The tissues to plasma concentration ratio and tissues to blood concentration ratio for lung was found to be time-dependent with 267.38 and 5.55 at 120 hours post-dose, respectively. A five-compartment model with first-order oral absorption and elimination best described the plasma, blood, and lung tissue pharmacokinetics. The estimated elimination rate constant (ke) for a typical monkey was 0.229 h-1. The volume of distribution in central (Vc/F) and other two peripheral compartments (Vb/F and Vl/F) were 115 L, 3.19 L and 4.87 L, respectively. Model-based simulation with PK parameters from cynomolgus macaques showed that the ratio of blood or plasma to lung tissue was a dynamic change course, which suggested that the rate of HCQ concentration decrease in blood or plasma was faster than that in lung tissue. HCQ was found to be accumulated in tissues, especially in liver, kidney, lung, spleen. Also, the tissues to plasma concentration ratio increased over time. The population pharmacokinetic model developed could allow for the assessment of pharmacokinetics-pharmacodynamics relationships, especially relevant tissue concentration-response for HCQ. Determining appropriate treatment regimens in animals allows translation of these to clinical studies.